THE CORRELATION BETWEEN ROLE AND FAMILY SUPPORT TOWARD THE BLOOD PRESSURE ON THE PATIENT HYPERTENSION IN TANJUNG ISUY VILLAGE KUTAI BARAT - ANNAAS BUDI SETYAWAN (Universitas Muhammadiyah Kalimantan Timur, 2019)
The role of the family is needed in providing support to hypertensive patients to be diligently checked themselves to the place of health care for regular blood control. One of the problems faced by the community, among others, is the lack of support and care from family members and the community in routine health checks. To know and see if there is a relation of role and support of family with blood pressure in hypertension patient in Tanjung Isuy village, Jempang Subdistrict of Kutai Barat Regency. The research method used in this study is a correlation study method with the cross-sectional approach, with a total sample of 35 people. Bivariate tests using the Spearman rank correlation test. The value of p-value from family role variables with blood pressure that is p = 0,000 <0.05 which means concluded that there is a significant relation between family roles with the blood pressure of hypertension patients. Family role with blood pressure that is p = 0.003 <0.05 which concluded that there is a significant relation between family support with a blood pressure of hypertension patient. There is a significant correlation between family role and support with blood pressure in hypertensive patients in Tanjung Isuy village, Jempang sub-district, West Kutai regency.